2014
DOI: 10.1016/j.freeradbiomed.2013.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 3A1 protects airway epithelial cells from cigarette smoke-induced DNA damage and cytotoxicity

Abstract: Aldehyde dehydrogenase 3A1 (ALDH3A1), an ALDH superfamily member, catalyzes the oxidation of reactive aldehydes, highly toxic components of cigarette smoke (CS). Even so, the role of ALDH3A1 in CS-induced cytotoxicity and DNA damage has not been examined. Among all of the ALDH superfamily members, ALDH3A1 mRNA levels showed the greatest induction in response to CS extract (CSE) exposure of primary human bronchial epithelial cells (HBECs). ALDH3A1 protein accumulation was accompanied by increased ALDH enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 36 publications
5
46
0
Order By: Relevance
“…It has recently been reported that ALDH3A1 is induced in bronchial epithelial cells by CS extract exposure in vitro [16]. To reconcile this experimental finding with the results of our study showing a depressed plaque ALDH activity in cigarette smokers, it should be considered that vascular antioxidant enzymes reportedly undergo an early prelesional induction and then a decreased expression in atherosclerotic lesions in vivo [17].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It has recently been reported that ALDH3A1 is induced in bronchial epithelial cells by CS extract exposure in vitro [16]. To reconcile this experimental finding with the results of our study showing a depressed plaque ALDH activity in cigarette smokers, it should be considered that vascular antioxidant enzymes reportedly undergo an early prelesional induction and then a decreased expression in atherosclerotic lesions in vivo [17].…”
Section: Discussionsupporting
confidence: 83%
“…To reconcile this experimental finding with the results of our study showing a depressed plaque ALDH activity in cigarette smokers, it should be considered that vascular antioxidant enzymes reportedly undergo an early prelesional induction and then a decreased expression in atherosclerotic lesions in vivo [17]. Moreover, various cell types may respond differently to noxious conditions including cigarette smoking [16]; indeed, while activated in bronchial epithelial cells [16], ALDH is instead inactivated by CS components in human blood cells as shown by Helander et al [18]. This latter finding is consistent with our results showing a depressed ALDH activity in human atherosclerotic lesions, where also blood cells are present.…”
Section: Discussionsupporting
confidence: 50%
“…UNCN3T cells were transduced with a lentiviral vector (cat#EX-A0312-LV152, pReceiver, GeneCopoeia, Rockville, MD) to overexpress CTGF protein as previously described (30). The transduced cells were selected with 5 µg/ml hygromycin for 14 days and surviving cells were collected.…”
Section: Methodsmentioning
confidence: 99%
“…CTGF-overexpressing or the control cells were cultured in p100 plates (100 mm) at a starting cell density of 15 × 10 3 /cm 2 and harvested after 3 d. Cell lysates were prepared in RIPA buffer with protease inhibitors (Boehringer Mannheim, Ridgefield, CT) and analyzed by immunoblotting as previously described (30). Protein levels were evaluated using anti-CTGF, anti-p53 antibody (Santa Cruz, CA) or anti-p16 and anti-p21 antibodies (Abcam, Cambridge, MA), and equal loading of protein samples from each group was evaluated using anti-β actin antibody (Sigma-Aldrich) after using the Restore WB stripping buffer (Thermo Fisher Scientific, Barrington, IL).…”
Section: Methodsmentioning
confidence: 99%
“…3 Rapid removal of aldehydes is essential to maintain the health of epithelial cells. 4 Tear film bears many similarities with lung-lining fluid of the alveoli, as these two structures are the only air-water interfaces in the human body. 5 Being in constant contact with surrounding air, tear film is also subject to similar ozone stress as the alveolar fluid, and therefore it is possible that increased ozone exposure may lead to ocular irritation through a similar mechanism.…”
mentioning
confidence: 99%